2007
DOI: 10.1007/s00248-006-9149-2
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Bradyrhizobium japonicum and B. elkanii Seven Years after Introduction of both the Exotic Microsymbiont and the Soybean Host in a Cerrados Soil

Abstract: The plasticity of rhizobial genomes is far greater than previously thought, with complex genomic recombination events that may be accelerated by the often stressful environmental conditions of the tropics. This study aimed at evaluating changes in soybean rhizobia due to adaptation to inhospitable environmental conditions (high temperatures, drought, and acid soils) in the Brazilian Cerrados. Both the host plant and combinations of four strains of soybean Bradyrhizobium were introduced in an uncropped soil dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
34

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 67 publications
4
45
0
34
Order By: Relevance
“…In addition, horizontal gene transfer between one inoculant strain of Mesorhizobium loti and indigenous strains of Mesorhizobium has been demonstrated under field conditions in New Zealand Sullivan et al , 1996. Increasing evidences of high rates of horizontal gene transfer in the soils of the Cerrados have also been reported (Galli-Terasawa et al 2003;Batista et al 2006) and might help to explain the high genetic diversity observed in several isolates of this study that were positioned in clusters showing very low genetic similarity in comparison to the inoculant strains (Fig. 1).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…In addition, horizontal gene transfer between one inoculant strain of Mesorhizobium loti and indigenous strains of Mesorhizobium has been demonstrated under field conditions in New Zealand Sullivan et al , 1996. Increasing evidences of high rates of horizontal gene transfer in the soils of the Cerrados have also been reported (Galli-Terasawa et al 2003;Batista et al 2006) and might help to explain the high genetic diversity observed in several isolates of this study that were positioned in clusters showing very low genetic similarity in comparison to the inoculant strains (Fig. 1).…”
Section: Resultssupporting
confidence: 71%
“…After some years of soybean cropping, a high percentage of strains belonging to unknown serogroups or showing highly dissimilar DNA profiles have been detected in Brazil (Santos et al 1999;Ferreira et al 2000;GalliTerasawa et al 2003;Hungria et al 2006;Batista et al 2006). For example, in the South Region, Ferreira et al (2000) reported that 38% of the strains belonged to unknown serogroups after 17 years of soybean cropping, and in the Cerrados that percentage was about 50% after some years of cropping (Galli-Terasawa et al 2003;Mendes et al 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A produção de muco altera a permeabilidade das células, tornando as estirpes mais resistentes a fatores bióticos de competição no solo, como a presença de microrganismos produtores de antibióticos. Batista et al (2007) Zhang et al (2007) obtiveram isolados de caupi de diferentes regiões da China e observaram, na coleção, por análises moleculares do gene ribossomal 16S, isolados com similaridade a Bradyrhizobium, Rhizobium e Sinorhizobium. Os autores identificaram, ainda, isolados com similaridade a Bradyrhizobium, mas que diferiram das espécies atualmente descritas no gênero, sinalizando para a possibilidade de pertencerem a uma espécie ainda não caracterizada.…”
Section: Materials E Métodos Materials E Métodos Materials E Métodos Matunclassified